2014
DOI: 10.1007/s11011-013-9476-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of neurocognitive outcomes on antiretroviral therapy after cryptococcal meningitis: a prospective cohort study

Abstract: Background Cryptococcal meningitis is the most common cause of adult meningitis in Africa, yet neurocognitive outcomes are unknown. We investigated the incidence and predictors of neurologic impairment among cryptococcal survivors. Methods HIV-infected, antiretroviral-naive Ugandans with cryptococcal meningitis underwent standardized neuropsychological testing at 1, 3, 6, and 12 months. A quantitative neurocognitive performance z-score (QNPZ) was calculated based on population z-scores from HIV-negative Ugan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 36 publications
1
63
2
4
Order By: Relevance
“…Subjects were prospectively enrolled in a study at Mulago National Referral Hospital in Kampala, Uganda, with appropriate IRB approvals and the written informed consent of the subjects or their surrogates. From November 2010 until December 2013, HIV‐infected persons with CD4 <200 cells/μL suspected to have meningitis were enrolled . Cryptococcal meningitis was diagnosed by CSF cryptococcal antigen detection via latex agglutination or lateral flow assay (ImmunoMycologics) and/or fungal culture.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects were prospectively enrolled in a study at Mulago National Referral Hospital in Kampala, Uganda, with appropriate IRB approvals and the written informed consent of the subjects or their surrogates. From November 2010 until December 2013, HIV‐infected persons with CD4 <200 cells/μL suspected to have meningitis were enrolled . Cryptococcal meningitis was diagnosed by CSF cryptococcal antigen detection via latex agglutination or lateral flow assay (ImmunoMycologics) and/or fungal culture.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to high mortality, cryptococcal meningitis has substantial morbidity. Survivors can suffer from irreversible blindness and deafness, as well as reversible neurocognitive impairments (5). …”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the repeat testing of neurocognitive function which showed improvement after 1 month of ART may have a component of improvement due to a practice effect, but overall appears quite promising for longer term function. As shown previously among cryptococcal meningitis survivors, their neurocognitive function normalizes to within one standard deviation of population norms within 1 year of ART [14]. Additionally, although meningitis was excluded in the HIV-infected control population, this population was not tested for CrAg.…”
Section: Discussionmentioning
confidence: 88%
“…On several measures of neurocognitive function, HIV-infected CrAg + persons did not differ significantly from survivors of cryptococcal meningitis who were tested at 1 month after meningitis diagnosis [14]. Secondly, longitudinal assessment of asymptomatic CrAg + persons found that they had significant improvement in neurocognitive function on most neurocognitive measures after the first 4 weeks of ART.…”
Section: Discussionmentioning
confidence: 99%